Answer: The required solution is (x, y) = (0, -5).
Step-by-step explanation: We are given to solve the following system of equations by the method of substitution or elimination :
![5x+3y=-15~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\-8x-2y=10~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)](https://tex.z-dn.net/?f=5x%2B3y%3D-15~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%28i%29%5C%5C%5C%5C-8x-2y%3D10~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%28ii%29)
We will be solving the given system by substitution method.
From equation (ii), we have
![-8x-2y=10\\\\\Rightarrow -4x-y=5\\\\\Rightarrow y=-4x-5~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(iii)](https://tex.z-dn.net/?f=-8x-2y%3D10%5C%5C%5C%5C%5CRightarrow%20-4x-y%3D5%5C%5C%5C%5C%5CRightarrow%20y%3D-4x-5~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~%28iii%29)
Substituting the value of y from equation (iii) in equation (i), we get
![5x+3(-4x-5)=-15\\\\\Rightarrow 5x-12x-15=-15\\\\\Rightarrow -7x=0\\\\\Rightarrow x=0.](https://tex.z-dn.net/?f=5x%2B3%28-4x-5%29%3D-15%5C%5C%5C%5C%5CRightarrow%205x-12x-15%3D-15%5C%5C%5C%5C%5CRightarrow%20-7x%3D0%5C%5C%5C%5C%5CRightarrow%20x%3D0.)
From equation (iii), we get
![y=-4\times0-5=-5.](https://tex.z-dn.net/?f=y%3D-4%5Ctimes0-5%3D-5.)
Thus, the required solution is (x, y) = (0, -5).